2008
DOI: 10.1038/nprot.2008.149
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy of supported lipid bilayers

Abstract: Supported lipid bilayers (SLBs) are widely used in biophysical research to investigate the properties of biological membranes and offer exciting prospects in nanobiotechnology. Atomic force microscopy (AFM) has become a well-established technique for imaging SLBs at nanometer resolution. A unique feature of AFM is its ability to monitor dynamic processes, such as the interaction of bilayers with proteins and drugs. Here, we present protocols for preparing dioleoylphosphatidylcholine/dipalmitoylphosphatidylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
169
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(183 citation statements)
references
References 40 publications
10
169
2
2
Order By: Relevance
“…For these tests, alamethicin was selected as the positive control due to its well-established in vitro pore-forming capabilities. Atomic force microscopy (AFM) (49) revealed that alamethicin induced deformation of membranes at 10 μM, similar to what has been described (50). In contrast, membranes treated with 10 μM of 1 were indistinguishable from untreated control membranes (Fig.…”
supporting
confidence: 80%
“…For these tests, alamethicin was selected as the positive control due to its well-established in vitro pore-forming capabilities. Atomic force microscopy (AFM) (49) revealed that alamethicin induced deformation of membranes at 10 μM, similar to what has been described (50). In contrast, membranes treated with 10 μM of 1 were indistinguishable from untreated control membranes (Fig.…”
supporting
confidence: 80%
“…S2) (25). A comparative analysis was performed on SLBs prepared by the surface deposition of AUV in aqueous solution using adapted protocols (26,29). Silicon wafers used as substrates were coated with a 9-nm layer of silicon dioxide to (i) support homogeneous and stable bilayers maintained in the fluid phase at room temperature and (ii) avoid charge build-up during SIMS measurements, which is necessary as SIMS relies on the detection of secondary ions extracted from the surface by a focused beam of primary ions ( 133 Cs + ) rastered across the sample (29).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, longer time and length scale studies are accessible in supported lipid bilayers (SLBs) (26). SLBs provide ideal experimental models for fluid-phase membranes and can be imaged by atomic force microscopy (AFM) (27,28).…”
mentioning
confidence: 99%
“…To characterize the interaction of AH peptide with the intact vesicle platform, QCM-D monitoring and atomic force microscopy (AFM) were employed as complementary techniques to respectively probe the interaction kinetics and morphological changes [82,88]. The adsorption of lipid vesicles onto solid supports results in the selfassembly of different lipid structures.…”
Section: Vesicle-to-bilayer Structural Transformation By Ah Peptidementioning
confidence: 99%